Experimental research on the structural optimization of grouting holes in circular and rectangular pipe sections for trenchless pipe jacking - Jiwei Wen; Yachen Ma; Tian Xiang; Minchuan Gan; Huilin Qiao; Wenhao Zhang; Dongyu Li; Jiale Wu; Zizhe Lu (Scientific Reports)
Abstract In trenchless pipe jacking engineering practice, the formation of high-quality slurry jacket on the outer wall of pipe section is the key to effectively reducing the pipe-soil frictional resistance, improving the construction efficiency, reducing the construction risk and ensuring the construction safety. Herein, the multifunctional experimental apparatus for the pipe-soil frictional resistance testing is improved to ensure the smooth implementation of the subsequent experimental research. The influences of the structural parameters of grouting holes in circular and rectangular pipe sections on the pipe-soil frictional resistance and the states of slurry jackets around the various pipe sections are investigated respectively based on orthogonal experiment. Key findings include the pipe-soil frictional resistances increase with the increase of the spacing between adjacent grouting holes and the deflection angle of grouting holes, the layout of grouting holes has the greatest influence on pipe-soil frictional resistance, reasonable and uniform layout of grouting holes around the pipe sections can form more complete high-quality slurry jackets, to show better pipe-soil frictional resistance reduction effect. Moreover, the optimal structural parameters of grouting holes in circular and rectangular pipe sections are the same, i.e. the layout is triple grouting holes, the spacing between adjacent grouting holes S is 417 mm, and the deflection angle of grouting holes α is 40°. These insights could provide some scientific and valuable guidance for pipe-soil frictional resistance reduction during trenchless pipe jacking.